Drivers of philanthropic foundations in emerging markets: family, values and spirituality - Giacomin, Valeria (Journal of business ethics, 2022)
This article discusses the ethics and drivers of philanthropic foundations in emerging markets. A foundation organizes assets to invest in philanthropic initiatives. Previous scholarship has largely focused on developed countries, especially the United States, and has questioned the ethics behind the activities of foundations, particularly for strategic motives that served wider corporate purposes. We argue that philanthropic foundations in emerging markets have distinctive characteristics that merit separate examination. We scrutinize the ethics behind the longitudinal activity of such foundations using 70 oral history interviews with business leaders in 18 countries in Africa, Asia, Latin America, and the Middle East. We find that 55 out of 70 foundations associated with these leaders have been used as vehicles for a specific type of philanthropic ethics defined as "spiritual philanthropy". These foundations often embodied personal or family traditions, culture, and religious values, which emphasized charitable giving and social responsibility. As in the case of many of the industrial foundations in Europe, these foundations also carried founding family names and provided a structure to maintain family control and enhance corporate reputation. We argue that, as business leaders in emerging markets are more directly exposed to dire social, educational and health deprivation than their counterparts in developed countries, they are less inclined toward grandiose world-making, and their foundations are more focused on delivering immediate benefits to communities in their home countries, motivated by implicit or explicit spirituality.